(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: Oral health care in pregnancy is often neglected by women and is also not appropriately addressed by prenatal and other health care providers and justify appropriate attention. The purpose of this cross sectional study was to describe percentage of oral disease occurrence and underlying causes in this sample of pregnant women. Methods: The study included 147 women aged between 15 to 49 years receiving prenatal care at the outdoor department of Azimpur Maternal and Child Health Training Institute in Dhaka, Bangladesh were invited to participate in this study from January 2013 to April 2013. Semi-structured interviews were conducted for data collection. Clinical exam data were recorded using validated scales in a special form. Results: Majority (72%) of the women were between 20 to 24 years. 57% had secondary school education. 88% of the women were unemployed and 52% women had very low family income of BOT s;10000. More than 90% of the women had good oral hygiene practices. However, 68% liked to have sugary snacks or drinks in between main meals, 7% visited their dentists during pregnancy , only 3% received advice for routine oral health screening from their prenatal care providers and only 4% women started their antenatal check-up during first trimester. All these negative influences might expose expecting mothers to high level of dental caries (54%), dental erosion (52%), gingivitis (100%) and periodontitis (27%). This study also showed that majority of the women acquired oral health information through watching television (61%) or reading newspaper (12%) while only 4% received information from doctors/dent ists throughout their lifetime. Conclusion: The undertaken research highlighted the importance of using media in modifying Bangladeshi pregnant woman’s behaviours toward oral health. It also emphasizes the need for inclusion of oral health preventive programme as part of pre and postnatal care. Further study in this area on a large scale will facilitate formulation of appropriate oral health policy to achieve satisfactory oral and general health outcomes during pregnancy and ensure optimum oral health conditions of their offspring. JOPSOM 2020; 39(1): 50-59